CONTROL OF AZEOTROPIC DISTILLATION COLUMN - EVANS SEBIT, PARIDE (IRC, 2017)
Azeotropic distillation is one of the most vital techniques that has been employed throughout the petrochemical and chemical processing industries for separation. A distillation column is one of the most common MIMO system challenging for control by PID controller. It is challenging to control both the composition of the top and bottom product without perturbing the composition of one another. Choosing the proper control approach for distillation columns and implementing it properly is very important. The challenge is anticipated to amplify when the distillation is azeotropic. The main difficulty to control an azeotropic column is due to its multiple steady state phenomena. In this project, the performance of a well-tuned linear PID controller is investigated when the column is operated around the azeotropic point. This will determine product purity. The case study simulation is based on Pilot scale distillation column block III UTP. In order to accomplish this project, a few methods are applied in which by first developing a binary azeotropic distillation column using Aspen HYSYS V8.0 software. Then the installation and tuning of PID controllers and finally the performance of the controller is investigated as the controlled variables reach the azeotropic point.